The implementation of ICT in teaching English by the teacher of MTS Swasta Al-Amin - Gumarpi Rahis Pasaribu; Sholihatul Hamidah Daulay; Zainuddin Saragih (English Language and Education Spectrum, 2023)
The purpose of this study was to investigate the many forms of technology that are utilized by instructors of English at MTS Swasta Al-Amin, as well as the various forms of ICT that are utilized by those teachers. This study employed a descriptive qualitative approach, with interviews and observations serving as the primary data collection tools. The observation was used to observe the English instructor, and the interview was used to learn about the types of ICT that were used by the teachers. This study focused on two educators in the seventh and eighth grades who used information and communication technology (ICT) into their English lessons. The findings of this study indicate that English instructors make use of many technological tools in their lessons, such as lcd monitors, laptops, speakers, the internet, google classroom, email, whatsapp, facebook, instagram, youtube, power point presentations, focus keys, Microsoft Word, and podcasts. The instructors favored using technology because it kept the students motivated and interested, as well as because it assisted the instructors in displaying materials, sending assignments, and providing notifications everywhere. According to the findings of the research described above, one may draw the conclusion that the integration of technology, specifically ICT, into the educational process has made it easier for educators to present, design, and develop instructional material and tools that are helpful for students' learning motivation.